2019
DOI: 10.1111/myc.12923
|View full text |Cite
|
Sign up to set email alerts
|

Would you like to purchase a rodent with dermatophytes?

Abstract: Summary The zoophilic dermatophyte Trichophyton benhamiae has received attention due to increasing infections in human in recent years. Trichophyton benhamiae has been found on asymptomatic rodents from pet shops in several countries posing a potential risk for transmission to humans. The aim of this study was to determine the prevalence of positive dermatophyte cultures from rodents in Danish pet shops in order to clarify the magnitude of potential sources of zoophilic infections and to prevent further spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…Nevertheless, some of the animals may have left their homes freely or have left the house with the owners. Therefore, the primary source of infections can be searched in the overpopulation of rodents in urban areas, potentially leading to transmission to domestic animals and further to humans [ 30 ]. One might also consider soil as a possible reservoir of this dermatophyte.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some of the animals may have left their homes freely or have left the house with the owners. Therefore, the primary source of infections can be searched in the overpopulation of rodents in urban areas, potentially leading to transmission to domestic animals and further to humans [ 30 ]. One might also consider soil as a possible reservoir of this dermatophyte.…”
Section: Discussionmentioning
confidence: 99%
“…Trichophyton benhamiae is a zoophilic dermatophyte that can cause highly inflammatory tinea in humans and animals [1]. Guinea pigs are the primary carrier, and other small animals are occasionally a source of infection [2]. Due to the increased variety of pets, T. benhamiae infection is rising.…”
Section: Introductionmentioning
confidence: 99%
“…3 Carriage studies conducted in Denmark on guinea pigs, hamsters and rabbits in pet stores have shown a 38% positive rate in guinea pigs, 6% in hamsters and 0% in rabbits. 4 In the case presented here, although the dog had no contact with guinea pigs, it did frequently hunt cavies (Microcavia australis), a wild rodent related to guinea pigs, which may have been the source of the contagion. The fungal species presents two phenotypes: one produces white colonies and the other yellow colonies.…”
Section: Discussionmentioning
confidence: 70%
“…Skin infections by T. benhamiae have been associated with inflammation in immunosuppressed children and adults, where it can lead to severe clinical signs with secondary bacterial infections, scarring and kerion celsi 3 . Carriage studies conducted in Denmark on guinea pigs, hamsters and rabbits in pet stores have shown a 38% positive rate in guinea pigs, 6% in hamsters and 0% in rabbits 4 . In the case presented here, although the dog had no contact with guinea pigs, it did frequently hunt cavies ( Microcavia australis ), a wild rodent related to guinea pigs, which may have been the source of the contagion.…”
Section: Discussionmentioning
confidence: 99%